2012
DOI: 10.1177/0305735612456727
|View full text |Cite
|
Sign up to set email alerts
|

The influence of stress, optimism, and music training on music uses and preferences

Abstract: In the present study we examined how different aspects of a person's life, such as the amount of stress experienced, levels of optimism, and the amount of musical training received, were related to their motives for listening to music (for emotional regulation and/or for cognitive stimulation) and their preferences for what types of music to listen to. Participants (N = 154) completed surveys measuring stress, optimism, music uses, and music preferences. Results indicate that high stress ratings predicted the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 65 publications
5
53
2
1
Order By: Relevance
“…Dispositional optimism as a personality trait is a general expectation of the individual that during lifetime they will encounter more of good than bad things (Scheier and Carver 1992). Only in one recent research did the authors suggest that optimism as a personality trait has an impact on the use of music for emotional regulation (Getz, Marks, and Roy 2014), while Popović (2006) states that the preferences for blues, classical, jazz, alternative and electronic music are associated with the structure of personality traits that belong to optimistic people. In this research we tried to explore the role of dispositional optimism/pessimism in musical preferences for different tempo and mode starting with the assumption that optimism is related to preference of fast music in major mode since those music characteristics is associated with happiness.…”
Section: Musical Characteristics Personality Traits and Musical Prefmentioning
confidence: 99%
“…Dispositional optimism as a personality trait is a general expectation of the individual that during lifetime they will encounter more of good than bad things (Scheier and Carver 1992). Only in one recent research did the authors suggest that optimism as a personality trait has an impact on the use of music for emotional regulation (Getz, Marks, and Roy 2014), while Popović (2006) states that the preferences for blues, classical, jazz, alternative and electronic music are associated with the structure of personality traits that belong to optimistic people. In this research we tried to explore the role of dispositional optimism/pessimism in musical preferences for different tempo and mode starting with the assumption that optimism is related to preference of fast music in major mode since those music characteristics is associated with happiness.…”
Section: Musical Characteristics Personality Traits and Musical Prefmentioning
confidence: 99%
“…People use music to manage their mood to a greater extent than they use other leisure activities such as reading or exercising (Lonsdale and North, 2011 ). However, the tendency to use music for mood repair may be influenced by music training considering that musicians use music for cognitive (e.g., attention to structural complexity or performing technique) rather than emotional reasons (Getz et al, 2014 ). To our knowledge, no study has yet investigated motivation for aesthetic experience with painting.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Lemont and Eerola (2011) reviewed the relationship between music and emotions. Getz et al (2014) conducted research on the effects of stress, optimism and music training on listening to music and preferences. The results showed that a high level of stress predicted the tendency for listening to music, while optimistic individuals were emotionally more inclined to listen to music.…”
Section: Resultsmentioning
confidence: 99%